Examining the Impacts of the Coronavirus Pandemic and Social Distancing on the Health of People With Mobility Disabilities - Goddard, Kelsey Shinnick; Schulz, Jonathan; Nzuki, Isaac; Hall, Jean P. (Frontiers in Public Health, 2022)
Objective To understand the effects of the coronavirus pandemic on the health and participation of people with mobility disabilities living in the community. Methods Participants responded to a survey designed to assess the effects of the coronavirus pandemic on their health and access to health care. Participants identified if various life situations were worsened, unchanged, or improved during the pandemic. Participants could provide further information on their improved or worsened lived experience in open-ended questions. Results A total of 39 people with mobility disabilities responded to the survey. Results indicate that many experienced a worsening of life situations related to health, including access to medications, health care services, and transportation. Conclusions Results show that many experiences were caused by the lack of appropriate policies, rather than the pandemic itself. Therefore, there is a need to modify pandemic preparedness plans and other policies to meet the needs of people with disabilities.